Body mass index and gestational weight gain: relevance in gestational diabetes and outcomes - A retrospective cohort study - Rosinha,Patrícia Mendonça Oliveira (2022)
ABSTRACT Objective: To evaluate the influence of maternal pre-pregnancy body mass index (BMI) and gestational weight gain (GWG) on blood glucose levels at diagnosis of gestational diabetes mellitus (GDM) and obstetric/neonatal outcomes. Subjects and methods: Retrospective cohort study including 462 women with GDM and singleton pregnancy delivered in our institution between January 2015 and June 2018 and grouped according to BMI/GWG. Results: The diagnosis of GDM was more likely to be established in the 1st trimester (T) in women with obesity than in normal-weight (55.8% vs 53.7%, p = 0.008). BMI positively and significantly correlated with fasting plasma glucose (FPG) levels in the 1stT (rs = 0.213, p = 0.001) and 2ndT (rs = 0.210, p = 0.001). Excessive GWG occurred in 44.9% women with overweight and in 40.2% with obesity (p < 0.001). From women with obesity, 65.1% required pharmacological treatment (p < 0.001). Gestational hypertension (GH) was more frequent in women with obesity (p = 0.016). During follow-up, 132 cesareans were performed, the majority in mothers with obesity (p = 0.008). Of the 17 large-for-gestational-age (LGA) birthweight delivered, respectively 6 and 9 were offsprings of women with overweight and obesity (p = 0.019). Maternal BMI had a predictive value only for macrosomia [aOR 1.177 (1.006-1.376), p = 0.041]. BMI and GWG positively correlated with birthweight (rs = 0.132, p = 0.005; rs = 0.188, p = 0.005). Conclusion: Maternal obesity is related with a major probability of diagnosis of GDM in 1stT, fasting hyperglycemia in 2ndT and a more frequent need for pharmacological therapy. Pre-gestational obesity is associated with GH, cesarean delivery and fetal macrosomia.